(untitled) (TAJ: Journal of Teachers Association, 2019)
Marked changes in maternal thyroid activity occur in pregnancy. During pregnancy bodily hormonal changes and metabolic demands result in complex alteration in the bio-chemical parameters of thyroid activities. Besides these, thyroid enlargement, increased thyroid capability for iodine uptake and increase in basal metabolic rate are evidential though these findings are not usually associated with symptoms of hyperthyroidism in pregnancy. Serum concentration of thyroid hormone thyroxine and triiodothyronine in complicated pregnancy like eclamptic toxemia is another field of controversy. To evaluate the changes in thyroid function in normal pregnancy and eclamptic toxemia, a study was undertaken in Rajshahi Medical College Hospital. We collected serum specimens from non pregnant but married women, normal 3rd trimester pregnant women and patients with eclampsia at 3rd trimester of pregnancy and measured serum concentrations of total and free thyroxine (TT4 & FT4) and total and free triiodothyronine (TT3 & FT3 ) by using RIA. Among the study subjects, 10 women were married but non pregnant, 12 women were in their 3rd trimester of normal pregnancy and 32 patients of eclamptic toxemia with 3rd trimester of pregnancy. In normal pregnancy, FT4 and FT3 levels remained normal while TT4 and TT3 levels were elevated. In patients with toxemia of pregnancy, the mean serum TT3 concentration was significantly lower than that of normal pregnancy and the serum FT3 concentrations were below the normal pregnancy range. The mean serum TT4 and FT4 concentrations in patients with eclampsia were however, significantly higher than those in normal pregnant women. TAJ 2018; 31(1): 9-14